Official Adobe print publishing guide - Lawler, Brian P. (Adobe Press, 2005)
THE KEY TO SUCCESSFUL PRINT PRODUCTION is an understanding of the entire workflow, from scanning and file creation through prepress and print production. Fully updated by author and publishing consultant Brian Lawler, The Official Adobe Print Publishing Guide, Second Edition, brings together the collective knowledge and wisdom of the experts at Adobe Systems in a simple, elegant presentation of the fundamental concepts and issues related to producing high-quality printed output. The book includes succinct, expertly illustrated explanations of the basic concepts and terminology of print production, along with Adobe's tried and true guidelines, tips, and checklists for ensuring a successful print job.